Peran Manajemen Pendidikan Islam dalam Penguatan Karakter Peserta Didik - Hidayat, Ervan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Islamic education management plays a significant role in strengthening students’ character development. This article explains how effectively designed and implemented educational management can support the character formation process through systematically organized stages of planning, implementation, and evaluation of educational activities. Character education is not limited to the development of cognitive abilities alone, but also encompasses moral, social, and spiritual dimensions, with exemplary noble character serving as the primary foundation of character building. This study employs a literature review approach by examining various scholarly sources, including books and journal articles that discuss educational management and character education from an Islamic perspective. The findings indicate that the success of students’ character development is strongly influenced by the integration of professional educational management, a supportive school culture, well-structured guidance and counseling services, and the active involvement of all stakeholders, including educators, parents, and the wider community. The optimal implementation of Islamic education management enables educational institutions to produce generations who are not only academically competent, but also morally mature, adaptable to contemporary challenges, possess noble character, and are capable of making constructive contributions to society and the nation. These findings affirm that Islamic education management is not merely an administrative function, but a strategic instrument in shaping students who are balanced intellectually, emotionally, socially, and spiritually.